Lượng giá giá trị du lịch sinh thái khu dự trữ sinh quyển Cát Bà sử dụng phương pháp chi phí du hành theo vùng - Nguyễn Hữu , Dũng; Nguyễn Thị , Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This paper investigates the economic value of natural-based tourism of Cat Ba biosphere reserve to recognize its potential economic benefits from ecotourism. Zonal travel cost method is utilized, with data collected from Cat Hai district People’s Committee and from 450 surveys conducted at various locations selected by stratified sampling method within Cat Ba biosphere reserve. The results show that the potential economic value of Cat Ba tourism is 18,453,294 million VND, partly of which is the consumer surplus of 9,220,110 million VND/year, and the tourism revenue generated from tourist spending of 9,233,184 VND/year. Such potential economic value of Cat Ba tourism is 10.2 folds higher than the current income from tourism of the local government. Cat Ba may reach its potential tourism revenue if its policy focuses on infrastructure development, leisure activity diversity, and natural conservation. This finding is of useful information for the policy makers to plan, manage, and build strategy for sustainable socio-economic development of the region.